Preliminary analysis of the transmission dynamics of Theileria parva in eastern Africa - Medley, G.F.; Perry, P.D.; Young, A.S. (Cambridge University Press, 1993)
Two mathematical models are developed that investigate the transmission dynamics of Theileria parva by the ixodid tickRhipicephalus appendiculatus to cattle in endemically stable areas. A method of estimating the rate of infection to cattle ofT. parva at the endemically stable state is given. Empirical estimates of ail the parameters in the model are available. The degree to which animals that have recovered from theileriosis (the ‘carrier’ state) are able to transmit the infection to tick nymphs or larvae is a crucial determinant of the dynamics of infection in a herd. Two control methods influencing the transmission of infection are considered – infection and treatment immunization and the reduction in tick feeding by acaricide application. The impact of each method on the transmission of infection is evaluated. Future developments and the data required to predict the dynamics of T. parva infections in cattle and ticks are discussed.